Combining mineral fertilizer and green manure for increased, profitable cassava production - Pypers, Pieter; Bimponda, W; Lodi-lama, J-P.; Lele, B; Mulumba, R; Kachaka, C; Boeckx, P.; Merckx, Roel; Vanlauwe, Bernard (Wiley, 2012)
Due to increasing population pressure and declining soil fertility, there is need for profitable alternatives to the slash-and-burn (SB) practice for cassava (Manihot esculenta Crantz) production in the humid lowlands of sub-Saharan Africa. Integrated Soil Fertility Management (ISFM) has high potential to deliver such options. Two on-farm, researcher-managed trials were installed to compare slash-and-burn with slashing and incorporation of the natural vegetation, and the application of green manure and/or NPK fertilizer at different rates. Root yields were comparable when the natural vegetation was slashed and incorporated, or slashed and burned. Fertilizer application increased yields by 42 to 212%, and had residual effects on a second cassava crop, increasing yields by 40 to 74%. Addition of green manure increased yields by 36 to 158%, without residual effects. Comparison with yields obtained in treatments where both inputs were applied in combination showed that yield increases due to fertilizer and green manure application were additive. Most profitable yield increases were obtained when fertilizer was applied in combination with Tithonia in the more fertile site, and in combination with Chromolaena or incorporation of the natural vegetation in the less fertile site. Net benefits were increased by 30 to 50% with a benefit cost ratio of $5 to $7 $?1 and a marginal rate of return of $4 to $5 $?1 relative to slash-and-burn. While current conditions favor combining fertilizer with green manure, an increase in labor cost or a decrease in fertilizer price would result in superior marginal rates of return for combining fertilizer with the natural fallow vegetation.